Experimental Learning Management to Improve Cognitive Aspects of Early Children with Kinesthetic Learning Style - Lilis Amperawati; Septiani Endang Yusnitasari (Journal of Childhood Development, 2024)
This research aims to explore the management of experimental learning methods based on kinesthetic learning styles in early childhood at RA Raudhatul Ummah, Bekasi City. The research method used is qualitative, with the research object focusing on learning practices at the institution. The research results show that learning management is a necessity that requires the application of management principles, including planning, organizing, implementing and supervising. In addition, the experimental method has proven to be very effective in improving cognitive aspects for children with a kinesthetic learning style. Research recommendations include suggestions to the Head of RA Raudhatul Ummah to carry out assessments from parents through questionnaires regarding experimental method learning activities and ensuring children's comfort. Apart from that, it is recommended that teachers continue to innovate in creating more varied learning methods, especially for children with learning styles other than kinesthetic. This research contributes to a further understanding of the importance of managing experimental learning and adapting learning methods to kinesthetic learning styles to improve the cognitive aspects of early childhood. Hopefully, these findings can become the basis for developing more effective learning approaches in similar educational institutions.